Physico-chemical properties and erosional behaviour of soil of Shahpur-Basdev watershed of district Hardoi treated under various conservation measures and land uses - PAL, MUNENDRA; KUMAR, MUNISH; KUMAR, KAUSHAL; SRIVASTAVA, ARUN (Journal of Soil and Water Conservation, 2020)
The present experiment was conducted under National Agricultural Innovation Project during the year 2008-2011 in district Hardoi, Uttar Pradesh. Maize fallowed by wheat crop was grown on contour across the slope during kharif and rabi season respectively. Strip-cropping is practiced consisting of long and narrow strip of erosion resisting crops grown across the slope. However cowpea was grown as cover crops in kharif season and gram in rabi in the projected area. Maize and wheat were grown with mungbean and chickpea as intercropping crops in field having slope less than 2%. The value of bulk density was found lower in the area where conservation measures applied in comparison to control (without conservation measures). The moisture equivalent, water holding capacity and water stable aggregates were observed to have slightly higher values in all soil conservation measures adopted in comparison to control plots. The slightly lower values of CEC in control in comparison to all cropping system might be due to higher clay content, more organic carbon in cropping system. Organic carbon, total nitrogen, available phosphorus and potash contents were recorded higher under all treatments over control. Dispersion ratio, erosion ratio and erosion index were found lower in all soil conservation measures adopted plots in comparison to control. Correlation coefficients (r) between sand, silt + clay and organic carbon and erosion ratio, sand contents showed significant positive with erosion ratio (r=0.8976**) and significant negative with erosion index (r=-0.8973**) and dispersion ratio (r=-0.8930**).